2011
DOI: 10.1016/j.schres.2011.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Atypical antipsychotic medications increase postprandial triglyceride and glucose levels in male rats: Relationship with stearoyl-CoA desaturase activity

Abstract: Recent preclinical and clinical evidence suggests that the stearoyl-CoA desaturase-1 (Scd1) enzyme plays a key role in the regulation of triglyceride (TG) biosynthesis and insulin sensitivity, and in vitro studies have found that antipsychotic medications up-regulate Scd1 mRNA expression. To investigate these effects in vivo, rats were treated with risperidone (1.5, 3, 6 mg/kg/d), paliperidone (1.5, 3, 6 mg/kg/d), olanzapine (2.5, 5, 10 mg/kg/d), quetiapine (5, 10, 20 mg/kg/d), haloperidol (1, 3 mg/kg/d) or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
(88 reference statements)
6
21
1
Order By: Relevance
“…In agreement with our results, Karen L.Teff et al[10] reported that olanzapine causes significant elevations in postprandial insulin, glucagon-like peptide 1, and glucagon coincident with insulin resistance in the absence of weight gain in healthy subjects. Moreover, decreased body weight has previously been observed in rats following chronic olanzapine or paliperidone treatment at specific dose[34]. Furthermore, numerous reports have documented hyperglycemia and new-onset type 2 diabetes in the absence of substantial weight gain inSGA-treated patients[6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, Karen L.Teff et al[10] reported that olanzapine causes significant elevations in postprandial insulin, glucagon-like peptide 1, and glucagon coincident with insulin resistance in the absence of weight gain in healthy subjects. Moreover, decreased body weight has previously been observed in rats following chronic olanzapine or paliperidone treatment at specific dose[34]. Furthermore, numerous reports have documented hyperglycemia and new-onset type 2 diabetes in the absence of substantial weight gain inSGA-treated patients[6].…”
Section: Discussionmentioning
confidence: 99%
“…olanzapine at 6 mg/kg body weight in rats produced a mean plasma concentration of 12.0±4.9 ng/ml at 3h after the last daily dose, which is comparable to the plasma concentration (above 9 ng/ml) that had a greater likelihood of clinical response[51]. Moreover, numerous reports showed that chronic daily treatment with olanzapine induced significant changes in adiposity and lipid metabolismin female rats[34,44,52]. Nevertheless, without the plasma olanzapine concentration data it remains possible that greater changes in FA profile may have been observed with a different mode of administration.…”
Section: Discussionmentioning
confidence: 99%
“…Although SCD1 is just a desaturase that catalyse the synthesis of monounsaturated fatty acids, previous studies have shown that the elevated SCD1 activity is implicated in a wide range of disorders, including obesity [41,42] and hepatic insulin resistance [43]. Moreover, evidence for up-regulation of Scd1 mRNA expression had been obtained in cultured human and rat cell lines following exposure to SGAs treatment [44,45], as well as in blood cells of patients treated with olanzapine [46]. Therefore, increased lipid accumulation caused by olanzapine was particularly likely due to the promotion of Scd1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents are commonly used to model antipsychotic-induced metabolic adverse effects, with hyperphagia and weight gain consistently replicated after subchronic olanzapine administration to female rats, either orally or via injections (Albaugh et al, 2006;Baptista et al, 1993;Choi et al, 2007;Goudie et al, 2002;MinetRinguet et al, 2006;Skrede et al, 2012a). Still, certain metabolic disturbances, such as antipsychotic-induced dyslipidemia, have not been convincingly modelled in rat (Boyda et al, 2010;Coccurello and Moles, 2010;Davoodi et al, 2009;Fell et al, 2007), although in a few recent experiments, olanzapine exposure led to increased serum triglyceride levels both in female (Skrede et al, 2012b) and in male (McNamara et al, 2011) rats. Discrepant findings in human and rat are likely related to species-specific aspects of energy and drug metabolism, in particular the short half-life (t 1/2 ) of olanzapine in rats -2.5-3 h, compared to the average 30 h in humans (Aravagiri et al, 1999;Callaghan et al, 1999;Mattiuz et al, 1997).…”
Section: Introductionmentioning
confidence: 99%